SEM Evaluation and Comparision of Marginal Integrity in Glass-Ionomer and Copmposite Class Restoratins With Immediate or Delay Polishing - Ranjbar Omidi B; Mirzaie M; Kermanshah H; Yasini E (Tehran University of Medical Sciences, 2011)
Background and Aims: Marginal seal in class V cavities and determining the best restorative material to decrease microleakage is of great importance in operative dentistry. The aim of this study was to evaluate the effect of polishing time on the microleakage of three types of tooth-colored restorative materials in class V cavity preparations and to assess the marginal integrity of these materials using scanning electron microscope (SEM).Materials and Methods: In this in vitro study, class V cavity preparations were made on the buccal and lingual surfaces of 30 bovine incisors (60 cavities). The specimens were divided into three groups each containing 10 teeth (20 cavities): group 1, Filtek Z350 (nanocomposite); group 2, Fuji IX/G Coat Plus (CGIC); and group 3, Fuji II LC (RMGI). In each group, half of the specimens (n = 20) were finished/polished immediately and the rest of them were finished/polished after 24 hours. All the specimens were thermocycled for 2000 cycles (5-50 °C). Epoxy resin replicas of 12 specimens (2 restorations in each subgroup) were evaluated using SEM and the interfacial gaps were measured. Finally, the teeth were immersed in 0.5% basic fuchsin dye for 24 hours at room temperature, sectioned and observed under stereomicroscope. The data were analyzed using Kruskal-Wallis and Mann-Whitney U tests and the comparison between incisal and cervical microleakage was made with Wilcoxon test.Results: Incisal and cervical microleakage were not affected by polishing time in none of the three restorative materials (P>0.05). Cervical microleakage only in Fuji IX with immediate polishing was significantly higher than incisal microleakage (P<0.05). Incisal and cervical microleakage with immediate or delayed polishing were not significantly different in Fuji IX, Fuji II LC, and Z350 (P>0.05).Conclusion: Immediate polishing is recommended in tooth-colored class V restorations.